Determination of glucose impurities in glucose-salt complex pharmaceutical products by HPLC-RID method: Analytical method development and validation study - Ergen, Harun; Gokekin, Yasin; Kartop, Remziye Azra; Ersen, Busra Cetin; Guleli, Muge; Kocaoba, Sevgi; Caliskan, Cem (ELSEVIER, 2025)
Pharmaceutical products containing glucose and salt are widely used in the health sector and play a vital role. These pharmaceutical products are usually encountered as a part of drugs used in treatment and medical procedures. However, the analytical determination and quantification of active ingredients and impurities belonging to active ingredients in such products is a complicated process. This is because the retention time of impurities belonging to the glucose molecule in these pharmaceutical structures and the presence of salts that give peaks in similar places complicate the analysis process. Moreover, when the British Pharmacopoeia (BP), European Pharmacopoeia (EP) and US Pharmacopoeia (USP) are examined, it is seen that there are only monographs belonging to glucose raw material and there is no record regarding the determination of impurities belonging to glucose in pharmaceutical products containing glucose-salt complex structures. A new method has been developed within the scope of the study to prevent this complexity. As a result of the method development studies, the specific solvent method was optimized and a relatively simple pre-purification process with high recovery was applied to avoid salt interference. In addition, high-precision determination and validation studies of glucose and its impurities were carried out using the High Performance Liquid Chromatography-Refractive Index Detector (HPLC-RID) method. This new analytical approach is expected to contribute to the development of reliable and high-quality products in the healthcare field by raising industry standards.
Keywords: HPLC-RID; Glucose; Glucose-salt complex; Oral rehydration solution; SUGARS; QUANTIFICATION; SEPARATION; FRUCTOSE; SUCROSE; Biochemistry & Molecular Biology; Chemistry